Realism: Structure & Illusion : Toward a Definition of Representational Art - Nasby, David; Macdonald Stewart Art Centre, Guelph; Burlington Art Centre, Burlington (Guelph : Macdonald Stewart Art Centre, 1981)
Astman, Barbara ; Beliveau, Paul ; Brodie, Jim ; Buff, Richard ; Carr-Harris, Ian ; Donoghue, Lynn ; Dyon, Annette ; Hall, John ; Harding, Noel ; Hutchinson, Nora ; Iveson, Robert ; Magee, David ; Maggs, Arnaud ; Moore, William ; Nutt, Ken ; Penny, Evan ; Richards, Phil ; etc.
Realism: Structure & Illusion : Toward a Definition of Representational Art, Macdonald Stewart Art Centre, Guelph, June 21 - July 26, 1981 / Burlington Cultural Centre, Burlington, June 21 - July 26, 1981
boek